2010
DOI: 10.1007/s10641-010-9624-y
|View full text |Cite
|
Sign up to set email alerts
|

Relationships among habitat, ecomorphology and diets of cichlids in the Bladen River, Belize

Abstract: The Neotropical Cichlidae is among the most species-rich and ecologically diverse groups of freshwater fishes. This study investigated interspecific morphological and ecological relationships within an assemblage of six cichlids in the Upper Bladen River, Belize. This portion of the river drains a nearly pristine watershed within a nature reserve, and thus should provide a natural ecological context for interpretation of ecological patterns. Species distributions within morphological, habitat and dietary space… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
42
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(46 citation statements)
references
References 34 publications
4
42
0
Order By: Relevance
“…The esophagus morphology is similar to the description by Gargiulo et al (1996) and Morrison and Wright (1999), for tilapias, which observed stratified epithelium with mucus-producing cells and striated muscle from the beginning to the end of the organ wall. The folds of the esophagus described for other teleosts (TAKASHIMA; HIBIYA, 1995;RANDAL;KUZ'MINA, 2000;SANTOS et al, 2007) were also observed in S. pappaterra.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…The esophagus morphology is similar to the description by Gargiulo et al (1996) and Morrison and Wright (1999), for tilapias, which observed stratified epithelium with mucus-producing cells and striated muscle from the beginning to the end of the organ wall. The folds of the esophagus described for other teleosts (TAKASHIMA; HIBIYA, 1995;RANDAL;KUZ'MINA, 2000;SANTOS et al, 2007) were also observed in S. pappaterra.…”
Section: Discussionsupporting
confidence: 87%
“…The most studied representatives of feeding or trophic morphological aspects of this family in Neotropical water are the Cichla (COCHRAN-BIEDERMAN; WINEMILLER, 2010, HELLIG et al, 2010SANTOS et al, 2011) and Oreochromis species (CACECI et al, 1997;MORRISON;WRIGHT, 1999;NJIRU et al, 2004), due to the importance for aquiculture and species of the subfamily Geophaginae (LÓPEZ-FERNÁNDEZ et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Codes, calculations and ecological significance of ecomorphological traits related to habitat use. For details of how measurements were taken see Cochran-Biederman & Winemiller (2010). All measurements were taken in millimeters (mm).…”
Section: Discussionmentioning
confidence: 99%
“…This raises the question of whether fish assemblages with low richness would really show the main ecomorphotypes associated with the use of food resources (Gatz, 1979;Winemiller, 1991;Breda et al, 2005;Oliveira et al, 2010). However, the fish assemblage of Jumelo stream included the main ecomorphotypes (benthic, nektonic and nektobenthic) that are found in other aquatic ecosystems with higher species richness (Casatti & Castro, 2006;Cochran-Biederman & Winemiller, 2010;Mazzoni et al, 2010;Oliveira et al, 2010).…”
Section: Discussionmentioning
confidence: 99%